Potential of an antioxidant combination Twendee X® to treat depressive disorders - Fukka You; Yoshiaki Harakawa; Toshikazu Yoshikawa; Haruhiko Inufusa (Archives of Depression and Anxiety - Peertechz Publications, 2023)
Depression and other neuropsychiatric disorders have major impacts on the daily life. These disorders are triggered by stress and obstacles stemming from changes in people's environment, relationships, finances, health, or in the case of many women, triggered by childbirth. An increase in the incidence of depression worldwide strongly correlates with modernization, economic downturns and the effects of major global events such as war and the COVID-19 pandemic. Despite the cause of the onset of depressive conditions, there is evidence that implicates Oxidative Stress (OS) as one of the major causes of depressive disorders. This strong association likely stems from the fact that compared to other organs, the brain is more vulnerable OS due to its high oxygen consumption, high lipid content, and weak antioxidant defense. In fact, decreased serum levels of antioxidants and a significant increase in MDA, a marker of lipid peroxidation, have been observed in depressed patients, indicating an elevated OS state. This state leads to not only cellular damage, but also inflammation and mitochondrial dysfunction. Therefore, addressing this lack of antioxidants could potentially alleviate depressive symptoms due to OS. Twendee X® (TwX) is a supplement that combines potent levels of eight active ingredients and has shown preventive effects in Alzheimer's Disease (AD). Studies using diabetes and aged mouse models, known risk factors for dementia, have shown that TwX has antioxidant capacity and mitochondrial protective effects, as well as inhibiting the age-related decline of neurogenesis and autophagy function. We theorized that these actions of TwX have been proposed to benefit depression by controlling OS. This literature review uses publications on PubMed and Google Scholar to explore the role of OS in psychiatric disorders and recent evidence of the therapeutic effects of antioxidants on such disorders. Publications also include those targeting TwX, which we theorize may be effective in neuropsychiatric disorders via its ability to possibly alleviate the effect of OS in the brain.